« Notre histoire compte » : Transmettre l’histoire des mouvements féministes et lesbiens à Genève - Carolina Topini; Isabelle Salem Diego Sentis (Glad!)
This article presents the approach and the stakes involved in the activist project « Our places, our parties, our fights: our history matters ». Dedicated to the collection and transmission of archives regarding the history of feminist and lesbian movements in Geneva, this project aims to provide a space for collective learning. The contribution creates a visual journey and a soundscape to introduce the reader to some pivotal moments of this little-known history: the provocative actions of the WLM-Geneva; the famous « bals des chattes sauvages »; the launch of the lesbian magazine Clit 007 (1980-1986); the 1982 «Goudou-Manif»; the radio broadcasts Sappho Revient and Canicule (1980s-1990s); the 8th ILIS conference in Geneva in 1986; the cafes, bars and nightclubs; the creation of the Natalie Barney Women's Center and Lestime.